The Interplay between Fear Reactivity and Callous-Unemotional Traits Predicting Reactive and Proactive Aggression - Nicholas D. Thomson; Sophie L. Kjærvik; Victoria J. Blondell; Laura E. Hazlett (MDPI AG, 2024)
Research has indicated that youths with CU traits are fearless, and this fearlessness plays a bidirectional role in both the development of CU traits and engagement in aggressive behavior. However, research specifically testing the role of fear in the association between CU traits and aggression is scarce. The goal of the current study was to test if fear reactivity, both conscious (self-report) and automatic (skin conductance reactivity; SCR), moderated the association between CU traits and aggression subtypes (reactive and proactive aggression). Participants included 161 adolescents (Mage = 15 years) diagnosed with conduct disorder. CU traits were assessed using the self-report Inventory of Callous-Unemotional Traits. Conscious and automatic fear reactivity were measured during a virtual reality rollercoaster using the Self-Assessment Manikin and skin conductance reactivity (SCR), respectively. Hierarchical regressions found that high fear reactivity on SCR moderated the link between CU traits and reactive aggression, while feeling more excited during fear induction moderated the link between CU traits and proactive aggression. Overall, a possible explanation of our divergent findings between conscious and automatic fear may be the difference between the instinctual biological response to threat versus the cognitive and emotional appraisal and experience of threat. Implications for intervention strategies targeting emotional recognition and regulation in reducing aggression in CD populations are discussed.